Microstructural study and differential scanning alorimetry analysis at elevated temperatures of uperheated as-cast A357 alloy - Mazlee, Mohd Noor; Shamsul, Baharin Jamaludin, Prof. Dr.; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr.; Shaiful Rizam, Shamsudin (University of Malaya, 2010)
Link to publisher's homepage at http://myais.fsktm.um.edu.my/